2020
DOI: 10.1136/bmjopen-2020-037614
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of pretreatment mean platelet volume in cancer: a meta-analysis

Abstract: ObjectiveOur study aimed to evaluate the prognostic and clinicopathological significance of pretreatment mean platelet volume (MPV) on cancer by using meta-analysis of published studies.DesignMeta-analysis.Data sourcesRelevant studies available before 22 December 2019 were identified by searching MEDLINE, EMBASE.Eligibility criteriaAll published studies that assessed the prognostic and clinicopathological significance of pretreatment MPV on cancer were included.Data extraction and synthesisStudies were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…While doing subgroup analysis including 7 studies, higher MPV levels were not associated with worse OS (NSCLC: HR 0.85, 95% CI 0.64 to 1.15). 14 Our study included 11 studies with NSCLC, SCLC, and NSCLC + SCLC, and similar to the above studies showed no statistically signi cant association.…”
Section: Discussionsupporting
confidence: 67%
“…While doing subgroup analysis including 7 studies, higher MPV levels were not associated with worse OS (NSCLC: HR 0.85, 95% CI 0.64 to 1.15). 14 Our study included 11 studies with NSCLC, SCLC, and NSCLC + SCLC, and similar to the above studies showed no statistically signi cant association.…”
Section: Discussionsupporting
confidence: 67%
“…In a subgroup analysis of seven studies, higher MPV was not associated with worse OS in NSCLC (HR = 0.85, 95% CI = 0.64–1.15). 14 Our study included 11 studies of patients with NSCLC and/or SCLC, whereas nine studies including only patients with NSCLC were included in the meta-analysis to reduce bias. Similarly as the aforementioned studies, no significant association between MPV and outcomes was observed.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] However, the correlation between platelet count/ size and lung cancer prognosis remains controversial because some studies determined that MPV is a poor prognostic factor in NSCLC whereas others suggested that MPV has no association with lung cancer. 11,[13][14][15] Thus, a robust analysis investigating the prognostic value of MPV among patients with lung cancer is needed. We conducted a meta-analysis to comprehensively evaluate the prognostic significance of MPV in this malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism for the decreased MPV in patients with PCa is not clear for us. It has been suggested that the level of MPV depends on the intensity of the systemic inflammation ( 21 , 22 ). Mild system inflammation leads to platelet activation and enhanced release of larger platelets, therefore elevating MPV level.…”
Section: Discussionmentioning
confidence: 99%
“…Mild system inflammation leads to platelet activation and enhanced release of larger platelets, therefore elevating MPV level. While severe system inflammation was associated with low levels of MPV due to increased release rate of small size platelets and selective consumption of large amounts of highly reactive large-sized platelets ( 21 ). The relationship between systemic inflammatory response and prostate cancer had been reported ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%